Weed Management of Horticultral Crops - Shanmugavelu; Aravindan; Rajagopal (Jodhpur Agrobios, 2010)
This book furnishes information on the mode of action of herbicides.
Weed Managent Fruit Crops Vegetable Crop Weed Crop
Keywords: Weed Managent, Fruit Crops ,Vegetable Crop